ANALISIS HUBUNGAN ATRIBUT EKOLOGI LAMUN DENGAN KUALITAS PERAIRAN DI TAMAN NASIONAL BALURAN KABUPATEN SITUBONDO - Sutadi Sutadi; Lilik Sulistyowati; Eko Sriwiyono (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Seagrass is one of the important ecosystems in coastal but it’s prone to damage by humans or natural factors. The existence of human activities, pollution and tourism activities in the coastal of Baluran National Park are factors that allow disruption of growth and changes of seagrass ecosystem. The study was conducted in May - June 2020 in order to identify the diversity of seagrass species, density, cover and correlations of seagrass attributes with the water quality in the Baluran National Park. (diversity, equitability and dominance) and the research was conducted at 6 stations. Seagrass observations using the "Quadrat Transect" method. Environment parameters include physical and chemical parameters such temperature, salinity, pH and dissolved oxygen, nitrates, phosphates and turbidity. The relationship between water quality and the ecological attributes of seagrass was analyzed using Pearson analysis (SPSS Statistics version 23). The results obtained 10 seagrass species that are Cymodocea rotundata Cymodocea serrulata. Enhalus acoroides Halodule pinifolia Halodule uninervis Halophila minor Halophila ovalis Syringodium isoetifolium Thalassia hemprichii and Thalassodnedron ciliatum. Seagrass cover which is included in the healthy category is station 6 with a cover value of 62% and station 3 by 61%, while station 1, station 2, station 4 and station 5 are in the less rich / less healthy category, Temperature and salinity parameters have a close relation between attributes of seagrass with water qualities. Temperature has a very strong of relation in index of diversity and index of equitability with a value of 0.856 and 0.824. The correlation coefficient (r) are 0.029 for diversity and 0.044 for equitability, while salinity has a strong relationship to equitability (0.878) with a value of correlation coefficient (r) is 0.022, and the other water qualities parameters have no significant effect. against seagrass.